Emphysematous pancreatitis presenting as new-onset diabetes mellitus with multi-organ dysfunction: Managed successfully with medical management alone - Singh, Nitesh Kumar; Ambinathan, Jaya Nath (Indian Journal of Case Reports, 2022)
Emphysematous pancreatitis is one of the rare and potentially fatal complications of acute pancreatitis. We present here the case of a 69-year-old man who presented with abdominal discomfort, vomiting, and constipation with features of sepsis due to Klebsiella pneumoniae bacteremia and new-onset diabetes mellitus. Elevated serum lipase levels and abdominal computed tomography scan showing pancreatic necrosis with air bubbles suggestive of emphysematous pancreatitis. He was managed conservatively as the surgical intervention was differed in view of unstable hemodynamics and thrombocytopenia. The entire emphysematous pancreatitis and sepsis resolved with medical management alone although surgical necrosectomy may be indicated at presentation.